Optimizing Students' Speaking Skills Through the Application of Contextual Teaching and Learning in Indonesian Language Learning - Muhammad Hunim; Asngadi Rofiq (KREDO : Jurnal Ilmiah Bahasa dan Sastra, 2025)
Students' speaking ability in Indonesian language learning is an important aspect that needs to be optimized. However, conventional learning approaches that are less relevant to students' lives often hinder the development of these skills. This study aims to analyze teachers' strategies, especially in the Muadalah Ulya Education Unit, in integrating the Contextual Teaching and Learning (CTL) method to improve students' speaking skills, identify challenges and solutions to the implementation of CTL, and evaluate the transformation of students' speaking skills after the implementation of this method. This research used a qualitative approach with a case study design, where data was collected through observation, interviews, and document analysis. The results showed that the implementation of CTL encouraged students to be more active in speaking through learning activities relevant to daily life. Challenges faced include time constraints, technology support, and differences in students' level of understanding, but these can be overcome through the preparation of flexible lesson plans and collaboration between teachers and students. Visible transformations include increased student courage in expressing opinions, more structured language use, and better understanding of the context of the conversation. This study found that the application of CTL method in Indonesian language learning is effective in optimizing students' speaking skills, while providing meaningful and contextual learning experiences. This research emphasizes the development of learning strategies that are relevant to the needs of students in the modern era.Â Â